Livros de artistas - Martins, Maria Clara Amado (1996)
The criteria that may determinate the selection of a particular theme for a search are related to their importance within the subject. The choice of Lygia Pape’s "Livros", as such for this writing just confirms the above mentioned assertion. This importance comes from the quality and the proeminency of her works in the nation’s cultural chapter as a member of the Neoconcrete Movement during the 50’s which left one of the most important legaçy to the brazilian modern art. The artist’s "Livros" work were four, all written between 1957 and 1960. They are the “Livros Poema", the "Livros da Criação”, the "Livros da Arquitetura" and the "Livro do Tempo”. The knowledge of such books will leed to the understanding of questions related to Poesia Concreta and Manifesto Neoconcreto, which marked the rupture between the Rio São Paulo’s concrete groups that had stablished polarity. "Livros" hints that they have a well defined spectator’s relation in both mental and physical planes. They all require the touch, the manipulation. From this premise on the analysis process took into consideration the understanding that art gets complete at the reception. That’s why this essay is supported in theoretic ground by thinkers which endeavoured in enlarging the perseption field and the reception theory- Merleau-Ponty and Mikel Dufrenne-, and also two others philosophers phenomenology field connected, Bergson and Bachelard. During this essay it became necessary to relate to works of artists of the same period, in order to feel the unique character of Lygia Pape’s work as well as stablish relation to others works of her such the "tecelares" (1954-1959), the "Ballet" (1958), and the "Ovo" (1968). The chose method to the present essay have established as priority to the analysis process the direct contact to the works, in accordance to Pierre francastel’s thinking that understand the works as a “plastic thinking" that must be found within itself not outside.